Sistem Informasi Posyandu Kabupaten Bireuen Berbasis Authorization Managament System - Fitri Rizani (Jurnal Tika, 2022)
The development of information systems technology that is increasingly developing contributes to other fields. Especially in the world of computers that have brought progress in various fields, Posyandu is a health activity organized from, by, and for the community assisted by Health Service officers of each district, especially in the villages of Paya Meuneng, Paya Reuhat, Gedong-gedong, Lancok, and Cot Ijue. In Bireuen Regency, the implementation starts from the Central Health Service officers coming to the villages according to the request. The Bireuen District Health Office has not fully utilized information technology in the Posyandu implementation process, where the implementing committee is still doing it manually, for pregnant women the data is collected using a book while for toddlers using a form, then pregnant women take measurements of height, arm circumference, weighing weight blood pressure, and examination of the womb, for Toddlers to carry out nutritional checks, measurement of height, arm circumference, and weighing. Data storage has not used a database, it is still being recapitulated using the Microsoft Excel application and then printed out as many times as needed, There are many system models in data management, one of which is the Autorization very suitable to be applied for data management of Posyandu activities, because every village again has to create a system from scratch